Предмет: Математика,
автор: Mrkapitowka
Упростите выражение: 2,3х-(2,3х+0,5)-0,2(5х-3)
Ответы
Автор ответа:
0
2,3x-(2,3x+0,5)-0,2(5x-3)=2,3x-2,3x-0,5-x+0,6=-x+0,1
Автор ответа:
0
вы исправили, так нечестно! я написал правильный ответ первее!
Автор ответа:
0
Тебе,что тоже нарушение поставить?
Автор ответа:
0
2,3х-(2,3х+0,5)-0,2(5х-3)=2,3х-2,3х-0,5-x+0,6=0.1-x
Автор ответа:
0
За хамство
Похожие вопросы
Предмет: Химия,
автор: ivanchek2019
Предмет: Литература,
автор: karo1458
Предмет: История,
автор: matveycrut20
Предмет: Математика,
автор: blinchik02